How to draw forest animals - Soloff-Levy, Barbara; Soloff-Levy, Barbara (Mahwah, N.J. : Watermill Press, 1985)
Step-by-step illustrations for drawing bears, foxes, birds, deer, bats, skunks, and other creatures that might inhabit a forest.
5 - 10 years
Keywords: Forest animals in art; Drawing -- Technique; Animals in art